The poetic discourse on “Serendib” in modern Arabic literature: Mahmoud Sami Al-Baroudi as a model - Mohammed Hafees, Mohammed Shareef; Rahmah Ahmad H. Osman, (Penerbit Universiti Kebangsaan Malaysia, 2024)
This article examines the impacts of Sri Lanka on the poetry of Mahmoud Sami Al-Baroudi, who was exiled there for more than seventeen years (1882-1899 AD). While no study has been done to reveal the extent to which the poet’s derivation from the Sri Lankan environment in his poetry, this research will attempt to clarify the poet’s approach in introducing Sri Lanka, showing the aspects of its nature, and then to discuss his poems about the Sri Lankan people. In order to accomplish these goals, the inductive method was used to track the verses and poems that addressed topics related to Sri Lanka, and then the analytical approach was employed to study and analyse those verses and poems. The study discovered that the poet followed the approach of ancient poets in defining Sri Lanka by using the name “Serendib”, which the Arabs called it in the past, rather than “Ceylon”, which was an official name at the time. Similarly, the poet’s admiration for Sri Lankan nature emerged, particularly the nature of “Kandy,” where he lived for nearly ten years of his life, and from which he derived imagery and ideas for his poetic production, that is, in some of the poems in which he is nostalgic for Egypt, as well as in two independent poems. Concerning the Sri Lankan people, the researcher discovered only some poetic verses in which the poet criticised the negative aspects of some of the people’s customs and cultures, as well as some of their moral and physical nature.